Development and validation of the Australian version of the Birth Satisfaction Scale-Revised (BSS-R). (1st January 2018) - Jefford, Elaine; Hollins Martin, Caroline J.; Martin, Colin R.
Abstract: Objective and background: The 10-item Birth Satisfaction Scale-Revised (BSS-R) has recently been endorsed by international expert consensus for global use as the birth satisfaction outcome measure of choice. English-language versions of the tool include validated UK and US versions; however, the instrument has not, to date, been contextualised and validated in an Australian English-language version. The current investigation sought to develop and validate an English-language version of the tool for use within the Australian context. Methods: A two-stage study. Following review and modification by expert panel, the Australian BSS-R (A-BSS-R) was (Stage 1) evaluated for factor structure, internal consistency, known-groups discriminant validity and divergent validity. Stage 2 directly compared the A-BSS-R data set with the original UK data set to determine the invariance characteristics of the new instrument. Participants were a purposive sample of Australian postnatal women ( n = 198). Results: The A-BSS-R offered a good fit to data consistent with the BSS-R tridimensional measurement model and was found to be conceptually and measurement equivalent to the UK version. The A-BSS-R demonstrated excellent known-groups discriminant validity, generally good divergent validity and overall good internal consistency. Conclusion : The A-BSS-R represents a robust and valid measure of the birth satisfaction concept suitable for use within Australia and appropriate for application to International comparative studies.